Sistemas de terminação de cordeiros do grupo genético pantaneiro - Villafuerte, Sergio Giovanni Espinosa (2016)
Pantaneiro genetic sheep group are native to the Pantanal Biome, in the Midwest region of Brazil, which is characterized by the production of meat. They are usually created under pasture, and the lambs usually finished in confinement. But should be considered sustainable and intensive finishing systems, adapted to the region. The aim of this study was to evaluate four finishing systems, including the productive performance and economic results as profitability indicators. Were used 54 lambs, 24 males and 30 females, wormed at weaning, with initial weight of 16.70 kg, with a mean age of 74 ± 9 days. Finishing systems were; Feedlot with corn silage (Zea mays) (CS) as roughage; Feedlot with mix corn silage and Pigeon pea (Cajanus cajan cv Mandarin) as roughage (CPS); Integration Crop-Livestock (ICL) grazing Brachiaria brizantha cv. BRS Piatã grass with Pigeon pea (Cajanus cajan cv Mandarin) in succession to mixed cultivation; stockpiled pasture (SP) with Brachiaria brizantha cv. BRS Piatã grass. All treatments the animals received energy-protein concentrate supplementation (16% CP and 82% TDN) equivalent to 2% of body weight. The experimental design was completely randomized in a factorial design, with four finishing systems and two sexes. The variables were final weight (FW) and average daily gain (ADG), and economic evaluation. Finishing systems under CS and ICL, obtained better productive performance not differing significantly from the CPS, which in turn did not differ statistically from SP. However, the economic evaluation demonstrated that the ICL and CPS systems were more profitable in finishing lambs. The pasture system formed in Integration Crop-Livestock with supplement of 2% of body weight, proved to be the most appropriate for the Midwest region in the finishing of Pantaneiro lambs in the dry season.